2 - Egyptian Parliamentary Elections: Between Democratisation and Autocracy: by Hala G. Thabet - Thabet, Hala G. (Africa Development, 2006)
The dissolution of the 1987 and 1990 parliaments, following two Supreme Court rulings that the 1984 and 1987 general elections were unconstitutional, and the transfer of the power to supervise elections from the police to the judiciary signalled an impending political opening, leaving the impression that there was political will to renew the rules governing elections and make them more trans- parent and equitable. The paper uses the 2000 elections to the People’s Assem- bly to assess the democratisation process in Egypt. It examines the extent of inclusion of all social forces and political parties, and of changes in popular participation. It argues that the 2000 elections bore the marks of electoral anoma- lies and manipulations which were characteristic of previous elections. Not- withstanding its flaws the 2000 elections marked a significant step in Egypt’s transition to liberal democracy.